Pengaruh Suit Game Perkalian Terhadap Kemampuan Numerasi Murid Kelas V SD Negeri Sokoharjo - Atikhah, Laila Miftakhul; Pangestika, Rintis Rizkia; Ngazizah, Nur (PAKAR Pendidikan, 2025)
Multiplication is a basic operation in mathematics and plays an important role in elementary school math learning to study increasingly complex mathematical content at the next levels. This research is based on the lack of numeracy skills among fifth-grade students at SD Negeri Sokoharjo, particularly in multiplication calculations. The main objective of this research is to determine the effect of the numeracy skills of fifth-grade students at Sokoharjo Public Elementary School through the use of multiplication rock-paper-scissors games. This study adopts a one-group pretest-posttest quasi-experimental design to investigate the effect on the population of fifth-grade students at SD Negeri Sokoharjo. The data collection techniques used include tests. All fifth-grade students were made the sample for the research. Quantitative data analysis is conducted using descriptive and inferential statistics, including normality tests, homogeneity tests, and hypothesis tests to examine the significance of the research results. This research was conducted by administering a pre-test before carrying out the multiplication suit game activity and a post-test after carrying out the multiplication suit game activity. Analysis of pretest and posttest data shows a significant increase in the average scores of the students. The initial score of 37.00 increased to 58.00 by the end of the study, indicating a rise of 21 points. Additionally, calculations using SPSS show a substantial increase with a significance value (2-tailed) of 0.008 < 0.05, indicating a significant change in pretest and posttest scores before and after the test. It can be explained that the use of multiplication rock-paper-scissors games has proven to improve the numeracy skills of fifth-grade students at SD Negeri Sokoharjo.